2019
DOI: 10.3390/ijms20051242
|View full text |Cite
|
Sign up to set email alerts
|

Increased iNOS and Nitrosative Stress in Dopaminergic Neurons of MDMA-Exposed Rats

Abstract: Several mechanisms underlying 3,4-Methylenedioxy-N-methylamphetamine (MDMA) neurotoxicity have been proposed, including neurochemical alterations and excitotoxicity mediated by reactive oxygen species (ROS), nitric oxide (NO), and reactive nitrogen species (RNS). However, ROS, NO, and RNS sources in the brain are not fully known. We aimed to investigate possible alterations in the expression of the ROS producer NOX enzymes (NOX2, NOX1, and NOX4), NO generators (iNOS, eNOS, and nNOS), markers of oxidative (8-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…The link between NOX‐2 and necroptosis or apoptosis of neurons is unclear, but LPS often induce Nos2 transcription, which increases NO• release (Arimoto & Bing, 2003; Fonseca et al, 2003; Medeiros et al, 2007). The produced NO• and ROS released from the NOX‐2 oxidase can form highly toxic RNS like peroxynitrite, which could directly lead to neurodegeneration (Dias, Junn, & Mouradian, 2013; Dingjan et al, 2016; Schiavone et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The link between NOX‐2 and necroptosis or apoptosis of neurons is unclear, but LPS often induce Nos2 transcription, which increases NO• release (Arimoto & Bing, 2003; Fonseca et al, 2003; Medeiros et al, 2007). The produced NO• and ROS released from the NOX‐2 oxidase can form highly toxic RNS like peroxynitrite, which could directly lead to neurodegeneration (Dias, Junn, & Mouradian, 2013; Dingjan et al, 2016; Schiavone et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A range of physiological (e.g., sweating, salivation, hyperthermia) and neuro-behavioural (e.g., psychomotor agitation, aggressiveness, convulsion) parameters were here assessed. Moreover, to highlight possible neurotoxic mechanisms, and similar to what previously investigated in relation to MDMA [23] the effects of 4,4 -DMAR on the expression of key markers of oxidative/nitrosative stress (8-OHdG, iNOS, NT and NOX2) and apoptosis (Smac/DIABLO and NF-κB) were here analysed. Furthermore, in taking from some current preliminary data, which showed the emergence of a 4,4 -DMAR-related hyperthermia, the expression of heat shock proteins (HSP27, HSP70, HSP90), markers related to heat-induced response [24][25][26], was here assessed as well.…”
Section: Introductionmentioning
confidence: 92%
“…The results of in vivo studies suggested the occurrence of phenomena related to CNS alterations (e.g., hyperthermia; seizures). By analogy to other stimulant drugs (e.g., MDMA [23] and cocaine [93]) we hypothesised that the oxidative and/or nitrosative stress occurred in the brain following the intake of 4,4 -DMAR.…”
Section: Immunoistochemical Studiesmentioning
confidence: 99%
“…[94] Nitric oxide-depleting myeloperoxidase (MPO) can maintain long-term NOS activity by preventing NO feedback inhibition. [95] On the other hand, myeloperoxidase has an important role in the host's defense against glioblastoma multiforme (GBM), as its inhibition worsens survival after radiation therapy in an animal model of glioblastoma. [96] Therefore, NO is involved in numerous processes that promote glioma growth.…”
Section: Molecular Mechanisms Of Free Radical Generation In Tumor Cellsmentioning
confidence: 99%